Developing and evaluating psychological provision in the acute hospital setting for patients with chronic respiratory disease - Thew, G; MacCallam, J; Salkovskis, P; Suntharalingam, J (Cambridge University Press, 2017)
Physical health outcomes for patients with long-term conditions can be significantly affected by their psychological wellbeing; those experiencing psychological difficulties are less able to manage symptoms, have a poorer quality of life, and more frequent hospital admissions. National guidance recommends the assessment and treatment of psychological difficulties secondary to respiratory disease, but implementation of this across services is inconsistent. Here, we describe the process and findings of a nine-month study integrating psychological assessment and intervention into an acute respiratory department. The aim of this provision was to provide appropriate interventions for both inpatients and outpatients with identified psychological needs, and to evaluate the impact of these across a range of outcome domains. Psychological assessment and intervention was flexibly implemented as clinically appropriate within the context of the wider multidisciplinary team. Hospital admissions data were collated, and feedback obtained from both patients and staff. Results highlighted that psychological provision was well received by both patients and staff, and was associated with improved patient experiences and a greater focus on holistic care. Of the 73 patients receiving psychology input with at least one month follow-up data, 75% showed a reduction in their admission frequency following intervention. The estimated savings to the wider NHS exceeded the costs of providing psychology input. In light of existing literature, national guidance, and the present findings, we highlight the need for those commissioning and managing respiratory services to consider the various potential benefits of integrating psychological provision for a patient group with high levels of psychological need.